TINJAUAN JOB DESCRIPTION HR-GA MANAGER DALAM MENANGANI PERJALANAN DINAS MANAGING DIRECTOR KE LUAR NEGERI DI PT BRIDON CIBITUNG – BEKASI - Widiawati, Kristiana (STIKS Tarakanita, 2017)
Some of the activities carried out by HR-GA Manager in handling The official travel of executive leadership include searching information by accepting form request for travel from the Managing Director. Preparing the official travel plan, HR-GA Manager does not assist the Managing Director in making the official travel plan. Managing Director develops his official travel plan based on the contents of the request for travel form. HR-GA Manager prepares transportation, accommodation and documents. Preparation of documents HR-GA Manager only prepares documents related to official travel only, and is followed up by travel agents, if passport, exit permit, and visa are no longer valid. The Managing Director takes care of his own official travel budget. During implementation official travel of executive leadership, HR-GA Manager helps the Managing Director remotely during business trips until the time of his return. The Managing Director reports the results of the official travel and financial reports performed on their own, and does not have any specific templates for reporting.